ANALISIS PENGARUH LABA BERSIH, SALES GROWTH, KEPEMILIKAN MANAJERIAL, DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN - Hutagalung, Manasye Benedicta Brigastara; Setiawati, Loh Wenny (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2019)
Dividend policy is a management decision of a company in determining the amount of dividend to be distributed to shareholders. Investors who have long-term goals will choose a return in the form of dividends in large quantities or relatively stable to reduce the uncertainty of investors who have invested their funds in the company. This research uses multiple linear regression analysis that will test the influence of net income, sales growth, managerial ownership, and leverage to dividend policy. The samples used in this study were 75 manufacturing companies listed on the Indonesia Stock Exchange for the period 2016–2018. The results of this research indicate that net income has a significant effect on dividend policy, while sales growth, managerial ownership, and leverage do not have a significant effect on dividend policy.